2014
DOI: 10.1002/j.0022-0337.2014.78.9.tb05803.x
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Pharmacy Observation Activity for Third‐Year Dental Students

Abstract: Interprofessional learning is a key component of today's health sciences education. Within a two-course series in dental pharmacology and therapeutics, a dental curriculum was revised to provide an interprofessional activity to expose dental students to a community pharmacy setting. The objectives of this activity were to augment students' learning about drug laws and prescription writing, as well as to foster interprofessional relationships and collaboration between pharmacists and dentists. Dental students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Implementing innovative learning techniques in a dental curriculum, such as interactive sessions with pharmacists, can be a good alternative. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Implementing innovative learning techniques in a dental curriculum, such as interactive sessions with pharmacists, can be a good alternative. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…16 Dentistry students observing a community pharmacy setting enhanced their pharmacology knowledge, found opportunities for collaboration and developed an appreciation for the roles a pharmacist plays in areas such as tobacco cessation, prescription errors and dosage formulation for children. 1 Another study showed that having both pharmacy students and dentistry students in a dental clinic allowed opportunity for increased identification of high-risk patients, such as those with diabetes or tobacco smokers. 6 Pharmacy and dental students at the University of Otago, New Zealand have initiated practicing together to discuss the dental care and medication history of patients within dental clinics to enhance their learning and improve patient outcomes.…”
Section: Clinical Settings or Rotationmentioning
confidence: 99%
“…These themes are not entirely discipline-specific but were particularly noted within the two professions in the IPE literature. 1,[4][5][6]12,14,16,17,20,21,[24][25][26][27]29,33,[39][40][41][42][43] Developing a national network, such as the European Interprofessional…”
Section: Barriers and Facilitators To Interprofessional Education For Dentistry And Pharmacy Studentsmentioning
confidence: 99%
“…Despite the identified benefits of pharmacist-dentist interprofessional collaboration, a review of the literature illustrates that routine collaboration between the professions is lacking. 1 , 5 , 12 , 20 , 23 28 . Thus far there have only been six studies published in this area.…”
Section: Introductionmentioning
confidence: 99%